UPAYA PELESTARIAN LINGKUNGAN PESISIR DALAM NOVEL TANJUNG KEMARAU KARYA ROYYAN JULIAN - Apriliadi, Frans; Efendi, Anwar (Jurnal Pendidikan Bahasa dan Sastra, 2018)
This study aims to explain the environmental conservation efforts of coastal areas in the Tanjung Kemarau novel by Royyan Julian with ecocriticism perspective. The method used in this research is descriptive qualitative by using data tabulation and researchers themselves as instruments. The data obtained were tested for content validity and reliability and then were analyzed based on four stages: data collection, data reduction, data presentation, and conclusions. The results showed that efforts to conserve the coastal environment were classified into two: the mitigation of environmental damage and the anticipated environmental damage. First, efforts to conserve the environment through mitigation was conducted by stopping the use of trawl nets. Second, environmental conservation efforts through anticipation is conducted by refusing the shifting of the mangrove forest function, back to nature, the myth, beliefs in the myth, and the sea quotation ceremony. Based on the discussion conducted showed that the Tanjung Kemarau novel establish the importance of safe guarding the environment based on cultural identity based on the values of local wisdom.